Les héritiers incertains. L’incapacité juridique face à l’épreuve de la discontinuité patrimoniale (Valachie, fin du XVIIIe siècle - début du XIXe) - Andreea-Roxana Iancu (L'Atelier du CRH)
The starting point of our analysis is the creation, in 1814, at the request of the great boyards of Ioan Caradja’s Divan, of a new department the purpose of which was to protect the estates of the prodigal minor children of the boyard-houses, even though an institutional guardianship mechanism (Epitropia obștească) was already in place. This institution would prepare the ground for a reframing, in 1818 and again in 1833 –in relation to Byzantine law–, of the legal incapacity, especially of the prodigals and of those “without reason”. Prior to 1818, legal practice shows, among other things, a superimposition of the two categories of incapacitated persons, as well as an alternative to disinheritance as a sanction for emancipated prodigal minors: placing the heir under guardianship in order to protect his descendants. In this case, the concepts of emancipation of the minor, majority, capacity and the exercise of ownership rights were interpreted by the different actors. We propose to grasp, at the level of legal practice, on the one hand the changes in the reconfiguration of the categories of incapacitated persons and, on the other hand, to analyse how the physical/psychic/social fragility of the incapacitated person threatened continuity and how family strategies and the intervention of the public authority tried to cope with it. The central question of our approach, then, will be: How to deal with the uncertain condition of the transmission of hereditary property?